Genome-wide analysis of PDX1 target genes in human pancreatic progenitors - Xianming Wang; Michael Sterr; Ingo Burtscher; Shen Chen; Anja Hieronimus; Fausto Machicao; Harald Staiger; Hans-Ulrich Häring; Gabriele Lederer; Thomas Meitinger; Filippo M. Cernilogar; Gunnar Schotta; et al. (Elsevier, 2018)
Objective: Homozygous loss-of-function mutations in the gene coding for the homeobox transcription factor (TF) PDX1 leads to pancreatic agenesis, whereas heterozygous mutations can cause Maturity-Onset Diabetes of the Young 4 (MODY4). Although the function of Pdx1 is well studied in pre-clinical models during insulin-producing β-cell development and homeostasis, it remains elusive how this TF controls human pancreas development by regulating a downstream transcriptional program. Also, comparative studies of PDX1 binding patterns in pancreatic progenitors and adult β-cells have not been conducted so far. Furthermore, many studies reported the association between single nucleotide polymorphisms (SNPs) and T2DM, and it has been shown that islet enhancers are enriched in T2DM-associated SNPs. Whether regions, harboring T2DM-associated SNPs are PDX1 bound and active at the pancreatic progenitor stage has not been reported so far. Methods: In this study, we have generated a novel induced pluripotent stem cell (iPSC) line that efficiently differentiates into human pancreatic progenitors (PPs). Furthermore, PDX1 and H3K27ac chromatin immunoprecipitation sequencing (ChIP-seq) was used to identify PDX1 transcriptional targets and active enhancer and promoter regions. To address potential differences in the function of PDX1 during development and adulthood, we compared PDX1 binding profiles from PPs and adult islets. Moreover, combining ChIP-seq and GWAS meta-analysis data we identified T2DM-associated SNPs in PDX1 binding sites and active chromatin regions. Results: ChIP-seq for PDX1 revealed a total of 8088 PDX1-bound regions that map to 5664 genes in iPSC-derived PPs. The PDX1 target regions include important pancreatic TFs, such as PDX1 itself, RFX6, HNF1B, and MEIS1, which were activated during the differentiation process as revealed by the active chromatin mark H3K27ac and mRNA expression profiling, suggesting that auto-regulatory feedback regulation maintains PDX1 expression and initiates a pancreatic TF program. Remarkably, we identified several PDX1 target genes that have not been reported in the literature in human so far, including RFX3, required for ciliogenesis and endocrine differentiation in mouse, and the ligand of the Notch receptor DLL1, which is important for endocrine induction and tip-trunk patterning. The comparison of PDX1 profiles from PPs and adult human islets identified sets of stage-specific target genes, associated with early pancreas development and adult β-cell function, respectively. Furthermore, we found an enrichment of T2DM-associated SNPs in active chromatin regions from iPSC-derived PPs. Two of these SNPs fall into PDX1 occupied sites that are located in the intronic regions of TCF7L2 and HNF1B. Both of these genes are key transcriptional regulators of endocrine induction and mutations in cis-regulatory regions predispose to diabetes. Conclusions: Our data provide stage-specific target genes of PDX1 during in vitro differentiation of stem cells into pancreatic progenitors that could be useful to identify pathways and molecular targets that predispose for diabetes. In addition, we show that T2DM-associated SNPs are enriched in active chromatin regions at the pancreatic progenitor stage, suggesting that the susceptibility to T2DM might originate from imperfect execution of a β-cell developmental program. Keywords: iPSC, T2DM, ChIP-seq, PDX1, SNPs, PP, GWAS